Aprendizagem da leitura e escrita: o estado da arte no período de 2010 a 2014 - Lupassa, Ezequiel Chassungo (2015)
Reading and writing are primary requirements for the exercise of the individual's right to citizenship in its operations in the literate world as autonomous. Objective: To make a current overview of the state of the art on the theme "learning to read and write." Methods: bibliographical research, whose collection consisted of raising the theses and dissertations deposited at the Digital Bank of Theses and Dissertations of the Brazilian Institute for Information in Science and Technology between 2010 and 2014. Working with data is divided into two phases: the first made up a statistical analysis, supported by SPSS version 22.0 for Windows program. In the second phase, the 18 theses that responded to the inclusion criteria, were read and analyzed according to content analysis proposed by Bardin (2006). Results: were found a set of 284 theses and dissertations, of which 98 formed the corpus of this research. Exclusion criteria sat down on another theme that initial literacy in any language other than Portuguese, in another area that teaching and other age group that child. Statistical analysis allowed for an overview of research in their distribution by area, by year, by state, by educational institution, by subject, by grade level and content categories. The theses content analysis reveals that there was a significant growth of research on this subject during the study period, which shows great interest and concern to the teaching of reading and writing practices in the early grades. The surveys allow us to observe a gradual evolution in the teaching of reading and writing practices of children in different methodological views. Conclusion: The research found aimed at improving teaching and reading and writing learning. The frequency of the themes articulated to the investments made by the government in relation to literacy and reading teaching practices and writing. But it is necessary to dare more in relation to the creation of pedagogical teaching methods that are able to meet the needs of students who are reading the ownership phase and writing, as well as investing more in teacher training, the intermediaries in this process